2021
DOI: 10.3389/fendo.2021.732456
|View full text |Cite
|
Sign up to set email alerts
|

PACAP–PAC1 Signaling Regulates Serotonin 2A Receptor Internalization

Abstract: Mice lacking pituitary adenylate cyclase-activating polypeptide (PACAP) display psychomotor abnormalities, most of which are ameliorated by atypical antipsychotics with serotonin (5-HT) 2A receptor (5-HT2A) antagonism. Heterozygous Pacap mutant mice show a significantly higher hallucinogenic response than wild-type mice to a 5-HT2A agonist. Endogenous PACAP may, therefore, affect 5-HT2A signaling; however, the underlying neurobiological mechanism for this remains unclear. Here, we examined whether PACAP modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, mutation of the Ser280 PKC phosphorylation site abolishes 5-HT 2A receptor signaling in response to LSD and DOI treatment, but not serotonin treatment (Karaki et al, 2014 ), highlighting the differential signaling induced by serotonin and putatively therapeutic hallucinogenic compounds. Finally, a recent study by Hayata-Takano et al ( 2021 ) identified that pituitary adenylate cyclase-activating polypeptide (PACAP) regulated the PKC and β-arrestin-dependent endocytosis of human 5-HT 2A , but not 5-HT 1A or 5-HT 2C , in HEK293 cells. In cortical neurons isolated from PACAP knockout mice, 5-HT 2A expression on the cell surface was increased, and these mice displayed a higher response to DOI compared to wild-type mice.…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mutation of the Ser280 PKC phosphorylation site abolishes 5-HT 2A receptor signaling in response to LSD and DOI treatment, but not serotonin treatment (Karaki et al, 2014 ), highlighting the differential signaling induced by serotonin and putatively therapeutic hallucinogenic compounds. Finally, a recent study by Hayata-Takano et al ( 2021 ) identified that pituitary adenylate cyclase-activating polypeptide (PACAP) regulated the PKC and β-arrestin-dependent endocytosis of human 5-HT 2A , but not 5-HT 1A or 5-HT 2C , in HEK293 cells. In cortical neurons isolated from PACAP knockout mice, 5-HT 2A expression on the cell surface was increased, and these mice displayed a higher response to DOI compared to wild-type mice.…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%
“…In cortical neurons isolated from PACAP knockout mice, 5-HT 2A expression on the cell surface was increased, and these mice displayed a higher response to DOI compared to wild-type mice. Importantly, Karaki et al ( 2014 ) and Hayata-Takano et al ( 2021 ) reveal the importance of PKC phosphorylation and receptor internalization in the signaling response of 5-HT 2A to serotonin and hallucinogenic compounds.…”
Section: Serotonin Receptor and Transporter Endocytosismentioning
confidence: 99%